NUTRITIONAL STATUS AND DRY MASS PRODUCTION OF ALFALFA IN FUNCTION OF POTASSIUM RATES IN TWO SOILS - Orioli Junior, Valdeci; Mendes Coutinho, Edson Luiz [UNESP]; Coutinho Neto, Andre Mendes [UNESP]; Cardoso, Saulo Strazeio [UNESP] (Univ Federal Uberlandia, 2014)
Potassium fertilization is very important to alfalfa crop in terms of yield, quality and persistence of forage, especially on soils naturally poor K. Thus, to assess the effects of K fertilization in alfalfa production and nutritional status, was carried out an experiment in a greenhouse using samples of a Dystrophic Oxisol medium texture (LV) (0.6 mmol(c) dm(-3) K) and a Dystrophic Ultisol sandy/medium texture (PVA) (2.2 mmol(c) dm(-3) K). A completely randomized design in a factorial arrangement 6 x 2 (six K rates and two soils) was used, with four replications. The K rates used were: 0, 25, 50, 100, 150 and 200 mg kg(-1) K. Potassium fertilization increased K content in soil and shoots. Dry matter production was increased with the K addition. However, in the PVA, this occurred only in the second cut. In LV, potassium fertilization increased N concentration in alfalfa shoots in both cuts. Plants with K concentration around 10 g kg(-1) had typical symptoms of this nutrient deficiency. The K critical levels of K in soil and shoots were 1.8 mmolc dm(-3) and 16.7 g kg(-1), respectively.
Keywords: Medicago sativa; Critical level; Potassium fertilization; Plant nutrition